Monitoring Wisconsin - Heynen, Nikolas C. (My University, 2005)
In the Winter 2005 issue of Monitoring Wisconsin, the Institute for Survey and Policy Research (ISPR) of the University of Wisconsin-Milwaukee (UWM) presents a summary of work in progress on universal free breakfast for children in Milwaukee by Dr. Nik Heynen of the UW-Milwaukee, Department of Geography.
Keywords: economics; wisconsin economy; free breakfast for children; inner city hunger; school meal program